Harmony with Nature: towards a new deep legal pluralism. Issue 1 (23rd April 2021) - Dancer, Helen
Abstract: Through a lens of legal pluralism, this article examines the histories, ontologies and discourses that have shaped two contrasting approaches to human-Earth relations in debates and legal frameworks for sustainable development. Anthropocentric discourses of nature as service-provider underpin the dominant approaches within ecology and economics. Ecocentric discourses of Nature as subject are reflected in Rights of Nature movements, particularly in the Americas, and at an international level, in the United Nations Harmony with Nature Programme. Drawing particularly on examples from forest governance in global and national contexts, this article analyses the ways in which international organisations and states have instrumentalised and embedded these discourses in law and policy and reflects on the challenges and possibilities for pluricultural legal orders, Rights of Nature and sustainable development. Moving away from conventional understandings of rights and entitlement to natural resources, the article argues for a deep legal pluralism that both decentres anthropocentric thinking on the environment and decentres the state in the development of Earth law. This places responsibility for the environment and the equitable sharing of power at the heart of legal frameworks on human-Earth relations and recognises the diversity of ontologies that shape these relationships in law and practice.